Las vallas publicitarias como productoras de discurso. - Andrade Flores, Juan Pablo (2016)
This article focuses on an analysis regarding billboards as producers of discourse, forms of communication and interpretation and the tools used as signs, from the appearance as billboards up its expansion into the world, later becoming one of the best forms of communication which is reported against the masses. The objective of this article is to analyze and interpret the billboards as producers of discourse, which arises performed through authors like Zapico (2012), Zecchetto (2002). Which are located in the United Nations Avenue between America and December 6th Avenue, as this sector is representative and several fences seen in him; in order to understand the complexity of all the signs and in turn issued the strategies employed by the various advertisements that will influence how you build speeches. The purpose of this article remains in developing a proposal based on the acquisition and interpretation of knowledge such as: the construction of speeches, production of meaning, interpretation of the sign and discourse, it is necessary to delve into the particulars contained in the subject, ie How speeches billboards are generated through the perception of the sign and the sense ?, analysis and reading the signs as; image, colors, people, texts, exposed as codes, tools that will be interpreted as potential generators speeches on billboards.